1992
DOI: 10.1093/oxfordjournals.annonc.a058183
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax following induction chemotherapy in patients with lung metastases: A case report and literature review

Abstract: A 29-year-old patient presented with bilateral pulmonary lesions following surgery for recurrent placental site trophoblastic tumor (PSTT). On day seven after institution of the 'EMA' regimen (etoposide, medium dose methotrexate with folinic acid rescue and actinomycin-D), complete pneumothorax occurred. Closed-system air drainage brought only transient lung expansion and subsequent talc pleurodesis was needed. During follow-up, complete regression of lung metastases was observed. A literature survey of post-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…4) developed spontaneous pneumothorax (SP) a few days after the first treatment. SP complicating chemotherapy has been reported mainly in chemosensitive metastatic tumors, such as osteogenic sarcoma, Wilms' tumor, and small cell lung carcinoma [18]. Only one patient with metastatic seminoma developing SP has been reported to date [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) developed spontaneous pneumothorax (SP) a few days after the first treatment. SP complicating chemotherapy has been reported mainly in chemosensitive metastatic tumors, such as osteogenic sarcoma, Wilms' tumor, and small cell lung carcinoma [18]. Only one patient with metastatic seminoma developing SP has been reported to date [19].…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient with metastatic seminoma developing SP has been reported to date [19]. The proposed pathophysiological mechanisms for SP complicating chemotherapy are related to rapid rupture of chemosensitive and peripherally (subpleural) located nodules with subsequent bronchopleural fistula, previous radiation to the lung, chemotherapy-induced lysis and impaired repair process, and increased intrathoracic pressure following emetogenic chemotherapy, particularly cisplatin [18,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas,mainlyosteosarcomas,appeartobethemalignancy most often associated with SP [1,2]. Apart from sarcomas, thiscomplicationhasalsobeenreportedinpatientswithlung metastasesfrommalignanciessuchasgermlinetumours,nonepithelialgynaecologicalmalignancies,insomepatientswith lymphomas and small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of cases had known lung lesion metastases or had a detectable lung lesion noted shortly after the SBSP occurred. The phenomenon has been reported in cases of metastatic sarcoma, trophoblastic tumor, non-seminomatous testicular cancer, and non-Hodgkin lymphoma [3][4][5][6][7][8][9][10] Sarcoma is most commonly associated with SBSP. One review examining 15 cases of SP after treatment with chemotherapy found an average time to develop SP after initiation of chemotherapy was 2-23 days [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several concepts have been proposed, including rupture of underlying coexistent emphysematous bullae; the presence of a cavitating tumor; a ball-valve effect of a tumor resulting in hyperinflation of alveoli; impaired healing in lung; tumor lysis or necrosis creating a bronchopleural fistula; and persistent local infection [5,7,11]. Biran et al [7] observed that certain chemotherapy regimens have higher rates of SP in some malignancies and theorized that the occurrence of an SP reflects a higher degree of activity of that drug against that particular tumor.…”
Section: Discussionmentioning
confidence: 99%